2018
DOI: 10.1111/dom.13489
|View full text |Cite
|
Sign up to set email alerts
|

Persistent elevations in circulating INS DNA among subjects with longstanding type 1 diabetes

Abstract: These results could reflect ongoing β cell death in individuals with longstanding T1D, even in the absence of detectable C-peptide production, suggesting that therapies targeting β cell survival could be beneficial among individuals with longstanding T1D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
(152 reference statements)
0
4
0
Order By: Relevance
“…Husseiny et al found that unmethylated INS DNA was also elevated following islet transplant [63]. Other recent studies have largely confirmed these initial observations and indicate that increased rates of β-cell death occur in T1D, aging, and islet transplantation [64,65].…”
Section: Considerations For Quantifying β-Cell Death In Human Diabetesmentioning
confidence: 86%
“…Husseiny et al found that unmethylated INS DNA was also elevated following islet transplant [63]. Other recent studies have largely confirmed these initial observations and indicate that increased rates of β-cell death occur in T1D, aging, and islet transplantation [64,65].…”
Section: Considerations For Quantifying β-Cell Death In Human Diabetesmentioning
confidence: 86%
“…Yet, only a few have examined evidence of β-cell death in subjects with either long-standing diabetes or in those at-risk for T1D. Using banked sera from subjects in the T1D Exchange registry, one study demonstrated elevations in both unmethylated INS and methylated INS in subjects from both C-peptide-positive and C-peptide-negative subjects with longstanding (≥9 years) T1D [ 37 ]. These findings seem indicative of the persistence of β cells in such subjects, where ongoing β-cell death may give rise to circulating unmethylated INS signals and ongoing systemic autoimmunity/inflammation may give rise to elevated methylated INS signals [ 38 ].…”
Section: Development Of Dna-based Biomarkers Of β-Cell Deathmentioning
confidence: 99%
“…Even direct evidence of beta cell death, using histological studies, has been difficult to demonstrate consistently [11, 23]. Recently, circulating cell-free unmethylated preproinsulin DNA (a proposed biomarker of beta cell death [5153]) was found to be elevated in a cross-section of 90 individuals with long-standing type 1 diabetes [54]. Although this marker may theoretically allow for analysis of beta cell death in living individuals, given the limitations of the sensitivity and specificity of this assay, combined with the likely tiny number of cells dying at any one time, interpretation of these data are challenging without longitudinal analyses in the same individuals.…”
Section: What Is the Source Of Persistent Beta Cells In Long-durationmentioning
confidence: 99%